PENERAPAN MODEL PEMBELAJARAN SNOWBALL THRAWING UNTUK MENINGKATKAN HASIL BELAJAR IPA TENTANG SUMBER ENERGI - Hartono Hartono (Universitas Islam Nahdlatul Ulama Jepara, 2017)
The purpose of this study was to determine the effect of improving learning outcomes with the application of snowball thrawing learning model in grade 4 students SDN 2 KandangrejoKlambu District Grobogan District 2015/2016 school year. From the preparation of the Proposal to the writing of the research results in February 2016 until April 2016. The subjects were 25 fourth grade students of SD Negeri 2 KandangrejoKlambu Sub-districtGrobogan District. Method is a way to simplify the workings of research andis a critical success factor of a study. The method used in this research is classroom action research method with through action as much as twocycles. Each cycle consists of four stages of planning, action, observation,and reflection. Data analysis used in this research using comparativedescriptive analysis that is by comparing the value of initial test results, the first cycle, and the second cycle. In the result of research and discussion of problem of researcher describe in general the location of research, research implementation both cycle 1 and cycle 2, result of research of cycle 1 and cycle 2, and discussion. Based on the data analysis conducted in this study obtained a conclusion that by applying the learning model of snowball thrawing can improve the learning outcomes of science energy sources in grade 4 students SDN 2 KandangrejoKlambu District Grobogan District 2015/2016 lesson year significant. The initial condition before the implementation of the average cycle of student scores was 60.87. In the first class action study cycle averaging value of 67.8, while cycle II obtained average value of 76.7. The increase of students' learning mastery from 40% in prasiklus, to 76% in cycle I and 92% in cycle II. Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan model pembelajaran snowball thrawing untuk meningkatkan hasil belajar siswa kelas pada siswa kelas IV SDN 2 Kandangrejo Kecamatan KlambuKabupaten Grobogan tahun pelajaran 2015/2016. Subjek penelitian adalah 25 siswa kelas IV SD Negeri 2 Kandangrejo Kecamatan Klambu Kabupaten Grobogan. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan melalui tindakan sebanyak dua siklus. Tiap siklus terdiri dari empat tahapan yaitu membuat perencanaan,melakukan tindakan, mengadakan pengamatan, dan melakukan refleksi.Analisa data yang digunakan dalam penelitian ini menggunakan analisisdeskriptif komparatif yaitu dengan membandingkan nilai hasil tes awal,siklus pertama, dan siklus kedua. Berdasarkan analisis data yangdilaksanakan dalam penelitian ini diperoleh suatu simpulan bahwa denganmenerapkan model pembelajaran snowball thrawing dapat meningkatkanhasil belajar IPA sumber-sumber energi pada siswa kelas IV SDN 2Kandangrejo Kecamatan Klambu Kabupaten Grobogan tahun pelajaran2015/2016 yang signifikan. Kondisi awal sebelum pelaksanaan siklus ratarata nilai siswa adalah 60,87. Pada penelitian tindakan kelas siklus 1 ratarata nilai 67,8, sedangkan siklus II diperoleh rata-rata nilai 76,7. Adanya peningkatan ketuntasan belajar siswa dari 40 % pada prasiklus, menjadi 76 % pada siklus I dan 92 % pada siklus II.